Private Enforcement of UK Competition Law: Enhanced Deterrence for Whom? - Caliskan, S. (Thomson Reuters, 2020)
The infringement of competition law by undertaking causes consumers and businesses to suffer financial loss. Private enforcement mechanisms however exist which aim at restoring them to the position they would have been in if the breach had not occurred. This strategy can, therefore, be beneficial not only in terms of providing an opportunity for victims to recover what they have suffered, but also in deterring the infringement of competition law undertakings. However, from the perspective of corporate governance, it may also give rise to an issue of risk distribution between companies and their directors. This article examines the private enforcement mechanism in UK competition law and argues that despite its aim of protecting those who are monetarily harmed due to an anti-competitive conduct of undertakings, it exposes companies to the risk of liability and loss when the directors of the firm are involved in the wrongdoing. The effect is that it may result in short-term benefits, but at greater expense to the firm in the long term. © 2020 Thomson Reuters and Contributors.
Keywords: Collective Proceedings; Competition Law; Corporate Liability; Deterrence; Directors' Liabilities; Directors' Powers And Duties; Infringement; Passing On; Private Enforcement